Mapa de localização: Projeto para uma área de estudo distrital - Aronés-Cisneros, Angel (2024)
This article proposes a design for a district location map that aligns with the political division of Peru. To achieve this, an exhaustive review of maps present in management plans, scientific articles, theses and other relevant documents was carried out. ArcGis 10.8 software was the primary tool used in creating the design. The main conclusion is that the design of the district location map must include secondary maps on the right side, showing the departmental, provincial and district levels. In addition, it is essential that the map contains basic elements such as the compass rose or the north arrow, the graphic scale and the reference system in UTM or geographic coordinates.